Application of X‐Ray Absorption Spectroscopy in Electrocatalytic Water Splitting and CO2 Reduction. Issue 9 (3rd August 2021) - Wang, Bin; Chu, Shengqi; Zheng, Lirong; Li, Xiaodong; Zhang, Jiangwei; Zhang, Fuxiang
Abstract : Renewable energy conversion and storage are crucial in aiding the worldwide efforts to replace fossil fuels and achieve carbon neutrality. In particular, electrocatalytic water splitting to obtain H2 and CO2 reduction to high‐value‐added fuels can lead to an epoch of hydrogen energy and a closed‐loop carbon cycle. Although many reported electrocatalysts have demonstrated outstanding performance at the laboratory scale, the origin of the superior electrocatalytic activity and selectivity and the structural evolution of these catalysts remain ambiguous. For this purpose, operando techniques are able to combine the characterizations of the catalyst with measurement of its performance under real working conditions. Herein, a critical overview of recent developments in understanding the underlying mechanisms of water splitting and CO2 reduction is presented, emphasizing the advanced operando X‐ray absorption spectroscopy characterization of these two electrocatalytic reactions. Some perceptions of the rising X‐ray technique directions and the foreground in this field are also presented. Abstract : A brief introduction on the application of X‐ray absorption spectroscopy (ex situ and in situ) in electrocatalytic water splitting and carbon dioxide reduction is systematically given, aiming to understand the structural evolution of electrocatalysts and plausible mechanisms in modulating the electronic and geometrical structures to improve the electrocatalytic activity and selectivity of these two reactions.